‘I am not Homophobic But...’: Disclaiming in Discourse Resisting Repeal of Section 28 - Burridge, Joseph (Sexualities, 2004)
This article attempts to take seriously the discourse of the morally conservative in the context of the failed repeal of Section 28 in the year 2000, and explores the operation of opposition to repeal which denied that homophobia was its motivation. It is argued that such disclaiming implies an orientation towards an attribution of homophobia as unhelpful or undesirable in this context. The failure of those advocating repeal to successfully problematize such arguments is deemed to reflect a collective ‘discourse of tolerance’ which assisted the arguments of those against repeal.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; homophobie; hétérosexisme; inégalités; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; section 28; soc2014; sociologie; systèmes d'oppressions; thématiques

L'hermaphrodite et la bisexualité à l'épreuve du droit dans l'antiquité - Cantarella, Eva (Diogène, 2004)
Keywords: LGBTQIA2+; androgynie; antiquité; approches et analyses; bisexualité; cours; discipline; discours dominant; europe; grèce; grèce antique; his4860; homosexualité; identités LGBTQIA2+; intersexuation; inégalités; moeurs sexuelles; mythologie; patriarcat; premier cycle; périodes historiques; rapports sociaux; rome antique; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques